Gestational Psittacosis With Secondary Hemophagocytic Syndrome: A Case Report and Literature Review - Sun, Li; Li, Pulin; Pang, Bo; Wu, Peipei; Wang, Ran (Frontiers in Medicine, 2021)
Gestational psittacosis and hemophagocytic syndrome (HPS) are rare clinical diseases. In this article, a case of gestational psittacosis concomitant with secondary HPS was reported. An analysis was performed on the clinical characteristics, signs, laboratory findings, progression, diagnosis, and treatment of a patient with gestational psittacosis concomitant with secondary HPS. Besides, the literature with respect to this disease was reviewed. This patient was definitively diagnosed through metagenomic next-generation sequencing techniques, bone marrow puncture and smear examination, and the determination of sCD25 level and natural killer (NK) cell activity. Anti-infectives such as doxycycline and etoposide combined with hormone chemotherapy achieved significant improvement in cough and expectoration, a return to normal temperature, and a significant improvement in oxygenation index. In addition, chest computed tomography revealed obvious absorption of lung lesions and a return of NK cell activity and sCD25 levels to normal ranges. Chlamydia psittaci pneumonia requires a clear determination of etiology, while HPS requires bone marrow puncture and smear examination, together with the determination of sCD25 level and NK cell activity in the blood. The findings of this study suggest that metagenomic next-generation sequencing is an effective instrument in clearly identifying pathogens that cause lung infection. Clinicians should consider atypical pathogens of lung infection in patients with poor response to empirical anti-infectives, and strive to design an effective treatment strategy as per an accurate diagnosis based on the etiology. As for patients suffering from long-term high fever and poor temperature control after broad-spectrum antibiotic treatment, non-infectious fever should be taken into account. A rapid and clear diagnosis would significantly improve patient prognosis.